The Role of Endothelial Dysfunction in Aortic Aneurysms - Siasos, Gerasimos; Mourouzis, Konstantinos; Oikonomou, Evangelos; Tsalamandris, Sotirios; Tsigkou, Vasiliki; Vlasis, Konstantinos; Vavuranakis, Manolis; Zografos, Thodoris; Dimitropoulos, Stathis; G. Papaioannou, Theodore; Kalampogias, Aimilios; Stefanadis, Christodoulos; et al. (Current Pharmaceutical Design, 2015)
Abdominal aortic aneurysm is a vascular disease which, despite the fact that it shares common risk factors with atherosclerosis, develops in parallel but as a partly independent process, through different pathogenic mechanisms. The pathogenic mechanisms involve metalloproteinase and collagenase activation, median and adventitial degradation, elastin lysis, vascular smooth cells transformation and apoptosis, collagen production and lysis imbalance combined with excessive inflammatory infiltration. Endothelial cells respond to a number of stimulating factors, including smoking, hypertension and AT1 receptor stimulation and non-uniform distribution of wall stress. Their ability to produce NO is crucial in order to adapt. Endothelial cells contribute to AAA development due to increased oxidative stress which is partly mediated by impaired NO bioavailability due to endothelial dysfunction and NADPH oxidase overexpression. In addition, they express several molecules among which adherence molecules, selectins, endothelin-1, regulating inflammatory infiltration and oxidative stress. Inflammatory cells consist of monocytes, polymorphonuclear neutrophils and lymphocytes and they are involved in the degrading process in the aortic wall by secreting proteolytic enzymesor by releasing interleukins which mediate the inflammation response. Endothelial dysfunction and arterial stiffness reflect on indices like FMD, carotid-femoral PWV and augmentation index, sometimes with controversial results. At present, surgical treatment is the only option provided in patients with large AAA, in particular. Focusing on the emerging role of endothelial cells in AAA pathology may contribute in creating new therapeutic options in a disease which has not yet a well-accepted, implemented pharmaceutical treatment.
Keywords: endothelium vascular